Modes of embodiment for an immersed experience in museums: The Royal Tank Museum. - Lama B Abuhassan; Shatha R Malhis (PLoS ONE)
This study examines how exhibits at the Royal Tank Museum (RTM) engage visitors through bodily experiences. The goal is to understand RTM's visitor interaction and engagement. This research fills a gap in the literature on Jordanian museums by documenting some experiential characteristics of museum exhibits and establishing a framework for evaluating embodied museum encounters. A detailed RTM episode analysis, online survey, visitor behavior observations, structured interviews, and a comprehensive questionnaire are used. Al-Karameh Hall offers embodied experiences using sensory and physical tools, while Jerusalem Hall and the Battle of Al-Latrun fall short due to fractured narratives and inadequate sensory engagement. According to the study, boosting the clarity of narratives, adding personal belongings, and strengthening the spatial connection between exhibitions and their surrounds can greatly enhance visitors' embodied experiences.